Validation of the conventional Glasgow Prognostic Score and development of the improved Glasgow Prognostic Score in patients with stage 0‐III colorectal cancer after curative resection - Satoshi Ishikawa; Norikatsu Miyoshi; Shiki Fujino; Takayuki Ogino; Hidekazu Takahashi; Mamoru Uemura; Hirofumi Yamamoto; Tsunekazu Mizushima; Yuichiro Doki; Hidetoshi Eguchi (Annals of Gastroenterological Surgery, 2021)
Abstract Aim Many inflammation‐nutrition scores, including the Glasgow Prognostic Score (GPS), have been reported as prognostic biomarkers in patients with colorectal cancer (CRC). We aimed to examine the predictive ability of the GPS and to improve the GPS. Methods We included a total of 438 patients with stage 0‐III CRC who underwent curative surgery from 2010 to 2013. They were divided into a training set comprising 221 patients and a validation set comprising 227 patients, according to the date of surgery. In the training set, the GPS was verified using a Cox regression model, and cut‐off values for C‐reactive protein (CRP) and albumin for relapse‐free survival (RFS) were calculated using receiver operating characteristics (ROC) curves. The improved GPS (iGPS) was developed with additional optimal cut‐off values. We also compared the iGPS with the conventional GPS in the validation set. Results The high GPS (GPS: 1‐2) was correlated with RFS and overall survival (OS) in the training set. Cut‐off values of CRP and albumin for RFS were 1.6 and 3.9, and we modified the GPS accordingly, adding the cut‐off values of 2 and 3.9 to CRP and albumin, respectively. In the validation set, a high iGPS was an independent prognostic factor for RFS (hazard ratio [HR]: 2.273; 95% confidence interval [CI]: 1.212‐4.364; P = .011), although the conventional GPS was not. Conclusion The iGPS was a more accurate prognostic predictor for patients with stage 0‐III CRC.